Aspectos metodológicos da determinação do índice de pobreza hídrica (iph) na bacia hidrográfica do salgado - Jorge, Rosa Lindjhenys de Oliveira (2024)
The effective management of water resources is recognized as a decisive challenge, especially in regions of water scarcity, such as the Brazilian semi-arid region. The Water Poverty Index (WPI) emerges as a central metric in this scenario, providing a comprehensive approach that goes beyond water availability. In this context, the present study proposes a detailed analysis of the application of WPI in the Salgado Hydrographic Basin, comparing the results with the previous work by Luna (2007). A bibliometric analysis on the WPI stands out to assess the evolution of scientific production on the topic. Additionally, seek to use Principal Component Analysis (PCA) to improve index accuracy, however, factorability tests suggested that the data is not suitable for this technique. The results indicated a critical situation in municipalities such as Jardim, Mauriti and Umari, while Baixio, Barbalha and Brejo Santo present better conditions. It is concluded that although there have been improvements since the study carried out by Luna (2007), additional interventions and management strategies are still permitted to ensure water sustainability in the region.